Biodegradation of bioplastics under aerobic and anaerobic aqueous conditions: Kinetics, carbon fate and particle size effect. (January 2022) - García-Depraect, Octavio; Lebrero, Raquel; Rodriguez-Vega, Sara; Bordel, Sergio; Santos-Beneit, Fernando; Martínez-Mendoza, Leonardo J.; Aragão Börner, Rosa; Börner, Tim; Muñoz, Raúl
Highlights: Only PHAs were aerobically/anaerobically biodegradable under aqueous conditions. PHB and PHBV yielded up to 496 and 480 Nm 3 of CH4 per ton, respectively. C-balance analysis for the different carbon sinks estimates polymer biodegradability. Mineralization rate depended on the total specific surface area of polymer. The modified Gompertz model accurately described bioplastic biodegradation. Abstract: The biodegradation of PHB, PHBV, PBS, PBAT, PCL, PLA, and a PLA-PCL blend was compared under aerobic and anaerobic aqueous conditions assessing biodegradation kinetics, extent, carbon fate and particle size influence (in the range of 100–1000 µm). Under standard test conditions, PHB and PBHV were biodegraded anaerobically (83.9 ± 1.3% and 81.2 ± 1.7%, respectively) in 77 days or aerobically (83.0 ± 1.6% and 87.4 ± 7.5%) in 117 days, while PCL was only biodegraded (77.6 ± 2.4%) aerobically in 177 days. Apparent biomass growth accounted for 10 to 30.5% of the total initial carbon depending on the bioplastic and condition. Maximum aerobic and anaerobic biodegradation rates were improved up to 331 and 405%, respectively, at the lowest particle size tested (100–250 µm). This study highlights the usefulness of analysing biodegradation kinetics and carbon fate to improve both the development and testing of biodegradable materials, and waste treatments in the context of a circular bioeconomy.